SEM Studies on Morphology and Function of Salt Glands in the Genus Tamarix L. (Tamaricaceae) from Iran - Arianmanesh, Reza; Mehregan, Iraj; Assadi, Mostafa; Nejadsatari, Taher (Asian Journal of Biological and Life Sciences, 2015)
The salt glands of halophytic plants are considered to be effective desalination devices and apparently maintain the salt balance in the leaves by the secretion of excess salts. These glands are also of particular interest since the mechanism of secretion is thought to be similar, if not identical, to the mechanism of ion transport which occurs in other parts of the plant.Thus, SEM studies were done on the morphology and function of salt glands of Tamarix species that grows in Iran. Salt gland in Tamarixis enclosed by a cuticular layer except in the two transfusionarea between the collecting cells and the lower pair of excretory cells. Thecuticle is separated from the walls of the excretory cells along the outersurface creating a collecting compartment. The present study revealed thatthis compartment appears to be separated into two cavities (one for each ofthe outer excretory cells) by extension of the cuticular layer inwards to thecentral anticlinal wall of the gland. Many species in Tamarix L. are halophytes with characteristics of salt-secreting. Salt glands play an important role in regulating iron balance, maintaining osmotic presser and improving salt endurance. Based on the multiply studies on salt glands, we take a review on the structure and function of salt glands of Tamarix L. in the paper.
Keywords: Iran; Salt glands; SEM; Tamaricaceae; Tamarix